Financial Sustainability of Public Sector Entities
XIX, 219 p. 7 illus.
Keywords: This book analyses the role of public sector accounting, and the relevance of accounting frameworks, in assisting financially sustainable policy making. Focussing on the European context, the book examines financial reporting, management accounting, budgeting and other reporting requirements, for example, Government Finance Statistics. It also analyses emerging forms of reporting, such as popular reporting and integrated reporting, which may also be considered by policy makers, standard setters, and managers of public sector entities. Josette Caruana is a Lecturer at the Department of Accountancy, University of Malta, Malta. Isabel Brusca is Professor in Accounting at the Department of Accounting and Finance, University of Zaragoza, Spain. Eugenio Caperchione is Professor of Public Sector Accounting at the Department of Economics, Modena and Reggio Emilia University, Italy. Sandra Cohen is Associate Professor of Accounting at the Department of Business Administration, Athens University of Economics and Business, Greece. Francesca Manes Rossi is Associate Professor of Accounting at the Department of Management and Information Systems, Salerno University, Italy.